2003
DOI: 10.1021/ic026206d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Porphyrins in the Presence of Acid-Labile Metalloporphyrins:  A New Route to Mixed-Metal Multiporphyrin Arrays

Abstract: The ability to incorporate distinct metalloporphyrins at designated sites in multiporphyrin arrays is essential for diverse applications in materials and biomimetic chemistry. The synthesis of such mixed-metal arrays via acid catalyzed reactions has largely been restricted to metalloporphyrins of stability class II (e.g., Cu, Co, Ni) or I. We describe routes for the rational synthesis of mixed-metal arrays via acid-catalyzed condensations that are compatible with metalloporphyrins of stability class III (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 75 publications
0
45
0
Order By: Relevance
“…S11b in the ESI †) due to a less remarkable demetallation effect, consistent with the LDI-HRMS analysis. Demetallation in pZnDPP and pMgDPP is not surprising since Zn 2+ and Mg 2+ are known labile cations 29 and the demetallation of the zinc(II) porphyrin was previously reported in the oCVD reaction of ZnDMP. 20 Evidence of demetallation followed by significant remetalation of the porphyrin core was observed in the LDI-HRMS spectra of the pAgDPP film that is dominated by the peaks related to fused iron porphyrin dimers [(FeDPP) 2 -7H-Cl] + (Fig.…”
Section: Reactivity Of Diphenyl-substituted Metalloporphyrins In Ocvdmentioning
confidence: 87%
“…S11b in the ESI †) due to a less remarkable demetallation effect, consistent with the LDI-HRMS analysis. Demetallation in pZnDPP and pMgDPP is not surprising since Zn 2+ and Mg 2+ are known labile cations 29 and the demetallation of the zinc(II) porphyrin was previously reported in the oCVD reaction of ZnDMP. 20 Evidence of demetallation followed by significant remetalation of the porphyrin core was observed in the LDI-HRMS spectra of the pAgDPP film that is dominated by the peaks related to fused iron porphyrin dimers [(FeDPP) 2 -7H-Cl] + (Fig.…”
Section: Reactivity Of Diphenyl-substituted Metalloporphyrins In Ocvdmentioning
confidence: 87%
“…Heterometallated porphyrin oligomers have been widely investigated as model systems for exploring electron transfer, 1820 energy transfer, 2124 nonlinear optical activity 25 and molecular recognition. 2628 The presence of an open-shell copper( ii ) ion in a porphyrin oligomer provides a local fluorescence-quenching site, due to relaxation via d–d transitions, although phosphorescence from trip-doublet states is sometimes observed.…”
Section: Introductionmentioning
confidence: 99%
“…The new strategy for determining hole‐transfer rates between nominally equivalent sites employs the ZnFbFb triads shown in Chart 3. The p ‐phenylene‐linked triad ZnFbFbΦ was prepared previously as part of a program to investigate new methods for synthesizing porphyrins under mild acid‐catalysis conditions (28). The triad ZnFbFbU contains diphenylethyne linkers and was prepared for the studies reported herein.…”
Section: Introductionmentioning
confidence: 99%